NEWEST RECOMMENDATION AND MECHANISM OF SODIUM-GLUCOSE COTRANSPORTER-2 INHIBITORS IN HEART FAILURE PRESERVED EJECTION FRACTION : A LITERATURE REVIEW - Yoseph Jeffry Hertanto (JURNAL WIDYA MEDIKA, 2023)
About 10 million people in Indonesia have been impacted by heart failure (HF), which is a complex clinical syndrome caused by insufficient cardiac output that is unable to meet the body's metabolic needs. The most frequent kind of HF, heart failure with preserved ejection fraction (HFpEF), has the fewest available treatments. Diuretics and SGLT-2 Inhibitors are the first-line treatments for HFpEF. This paper aim to determine the mechanism of sodium-glucose cotransporter-2 (SGLT-2) Inhibitors in HFpEF and the newest recommendation for it, so that it might be utilized as a reference for management in the future. This is a literature review study which conducting by gathering numerous books and journal articles which relevant with the topic. The mechanisms of SGLT-2 Inhibitors in HFpEF are not well understood, but some theories suggest that these medications affect preload, afterload, cardiac remodeling, blood pressure, arterial stiffness, and ketone body formation. They can also stimulate erythropoiesis, inhibit the myocardial Na+/H+ exchanger (NHE), and have anti-oxidant and anti-inflammatory effects, so they are no longer just seen as anti-diabetic medications. Recently, Perhimpunan Dokter Spesialis Kardiovaskular Indonesia (PERKI) published a Heart Failure guidelines and classify SGLT-2 Inhibitors as a class IB treatment for HFpEF.